The role of islamic education to address antisocial behaviors in students - Farkhan, Aulia; Nuryana, Zalik (Al-Misbah (Jurnal Islamic Studies), 2025)
This research examines the growing concern of students displaying antisocial behaviors, such as truancy and school suspensions, which stem from their disregard for teachers' advice. The study focuses on two main aspects: the efforts of MTs Muhammadiyah Kasihan in fostering Tawadhu' (humility) among students and the factors influencing its development. Employing qualitative research methods, this study aims to gain a holistic understanding of the experiences of research subjects, including their behaviors, perceptions, motivations, and actions within a natural context. The findings reveal that the madrasah cultivates Tawadhu' through teacher role models, handshaking etiquette, and continuous guidance. The development of Tawadhu' is influenced by various factors, including the family environment, school environment, and community environment. This research underscores the significance of nurturing humility in students as a means to mitigate antisocial behaviors, highlighting the crucial role of teachers and structured guidance in educational institutions. However, the findings are limited to the specific context of MTs Muhammadiyah Kasihan and may not be universally applicable. This study contributes to the understanding of Tawadhu' cultivation and its role in addressing student behavior, emphasizing the importance of teachers and the environment in shaping students' attitudes. The insights provided can inform educational institutions and policymakers in developing strategies to foster positive student behavior.